Chitin biological absorbable catheters bridging sural nerve grafts transplanted into sciatic nerve defects promote nerve regeneration - Wang, Zhi‐Yong (CNS Neurosci Ther, 2018)
AIMS: To investigate the efficacy of chitin biological absorbable catheters in a rat model of autologous nerve transplantation. METHODS: A segment of sciatic nerve was removed to produce a sciatic nerve defect, and the sural nerve was cut from the ipsilateral leg and used as a graft to bridge the defect, with or without use of a chitin biological absorbable catheter surrounding the graft. The number and morphology of regenerating myelinated fibers, nerve conduction velocity, nerve function index, triceps surae muscle morphology, and sensory function were evaluated at 9 and 12 months after surgery. RESULTS: All of the above parameters were improved in rats in which the nerve graft was bridged with chitin biological absorbable catheters compared with rats without catheters. CONCLUSIONS: The results of this study indicate that use of chitin biological absorbable catheters to surround sural nerve grafts bridging sciatic nerve defects promotes recovery of structural, motor, and sensory function and improves muscle fiber morphology.